Changes In Individual Functional Assessment Of Cancer Therapy–General Items Following a 12-Week Tele-Rehabilitation Program In Oncology: a Secondary Analysis - Preksha Jain; Dr. Jafar Khan; Dr. Manoj U. Mahajan; Dr. Veenodini Warhade; Dr. M.S Satish; Dr. k m Annamalai (PAIN, JOINTS, SPINE, 2026)
Introduction: Health-related quality of life (HRQOL) is a multidimensional outcome frequently used to evaluate rehabilitation interventions in oncology. Most tele-rehabilitation studies report improvements using total or domain-level scores of the Functional Assessment of Cancer Therapy–General (FACT-G) questionnaire; however, little is known about which individual patient-reported concerns are most responsive to structured tele-rehabilitation. Understanding item-level response patterns may provide clinically meaningful insights for tailoring rehabilitation programs and identifying persistent unmet supportive care needs.Methods: This secondary analysis used data from a prospective single-group feasibility study evaluating a 12-week supervised tele-rehabilitation program in adults receiving cancer care. Of 40 enrolled participants, five did not follow up and 35 were included in the first-versus-last analysis. HRQOL was assessed with the 27-item FACT-G. For each participant, the baseline/first response was compared with the last available follow-up response; for Vijay Goswami, who had two assessments, the second response was treated as the last response. Item-level mean scores, mean change, and proportions improving, remaining unchanged, or worsening were calculated. Paired changes were tested using two-sided Wilcoxon signed-rank tests with Holm adjustment across 27 items, using available-case analysis for item-level missing data.Results: Distinct item-level response patterns were observed. The largest mean improvements were in time spent in bed (+1.00), trouble meeting family needs (+0.83), pain (+0.83), enjoyment of usual recreational activities (+0.83), and feeling ill (+0.71). After Holm adjustment, six items remained statistically significant: time spent in bed (adjusted p=0.013), feeling ill (p=0.014), enjoyment of usual recreational activities (p=0.017), pain (p=0.039), trouble meeting family needs (p=0.043), and sadness (mean change +0.63; p=0.045). Coping, illness acceptance, family acceptance, and closeness to the main support person changed little. Satisfaction with sex life had only 16 paired responses and showed a nonsignificant negative mean change (−0.50; adjusted p=0.959).Conclusion: Item-level analysis demonstrated that tele-rehabilitation was associated with differential improvement across individual HRQOL components rather than uniform changes throughout the questionnaire. Physical symptom burden and functional participation appeared most responsive, whereas psychosocial and relationship-related concerns remained relatively stable. These findings may assist clinicians in identifying domains requiring additional supportive interventions and contribute to more individualized tele-rehabilitation programs.